2017
DOI: 10.1002/cam4.1205
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow biopsy superiority over PET/CT in predicting progression‐free survival in a homogeneously‐treated cohort of diffuse large B‐cell lymphoma

Abstract: Several studies have reported uneven results when evaluating the prognostic value of bone marrow biopsy (BMB) and PET/CT as part of the staging of diffuse large B‐cell lymphoma (DLBCL). The heterogeneity of the inclusion criteria and not taking into account selection and collinearity biases in the analysis models might explain part of these discrepancies. To address this issue we have carried a retrospective multicenter study including 268 DLBCL patients with a BMB and a PET/CT available at diagnosis where we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…To sum up, the focal pattern of BM is of better prognostic value than BMB. Unlike Chen-Liang 's and Khan's results, we didn't obtain the result that BMB was independently predictive for PFS and OS 14 , 19 . We found the BMB+ rate in our study and previous studies differed in a considerable disparity, ranging from 6.0% to16.4% 2 , 24 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…To sum up, the focal pattern of BM is of better prognostic value than BMB. Unlike Chen-Liang 's and Khan's results, we didn't obtain the result that BMB was independently predictive for PFS and OS 14 , 19 . We found the BMB+ rate in our study and previous studies differed in a considerable disparity, ranging from 6.0% to16.4% 2 , 24 .…”
Section: Discussioncontrasting
confidence: 99%
“…The finding of dPET+ of BM is not rare in DLBCL. In some studies, this kind of BM pattern was interpreted negative for BMI 2 , while some other researchers considered it as positive 11 , 19 , 20 . The disagreement on the interpretation made it difficult to accurately assess the value of dPET+ in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies confirm this prognostic impact 11,12 although for those patients who are stage IV by criteria other than BMI it seems that PET/CT-defined BM involvement loses its prognostic impact while BMB-defined BM involvement still predicts a worse outcome. 13,14 In this study, diffuse BM change on PET/CT was not deemed to indicate BM involvement, as per the predetermined methodology. None of the patients with a diffuse increase in BM uptake of FDG had a positive BMB.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reported recommendations about staging and response assessment in lymphomas (Cheson et al, 2014) indicate that morphologic examination of the BM trephine biopsy (BMB) in patients with DLBCL is only needed when BM infiltration is negative by positron emission tomography (PET) and the identification of occult discordant histology is clinically important. Nevertheless, recent publications have reported that BMB offer different and complementary clinical information in DLBCL patients (Adams & Kwee, 2015;Adams & Kwee, 2017;Avigdor, 2013;Chen-Liang et al, 2017).…”
mentioning
confidence: 99%